Responsabilidade social e satisfação do consumidor: um estudo de caso - ARAÚJO, Marley Rosana Melo de (Universidade Federal do Pará, 2012)
The theme of this study is the phenomenon of social responsibility in business. This research constitutes a case study with a socially responsible company, aiming at to verify the consumer's perception concerning the social responsibility of this company and its influence, together with some variables of business acting (price of the tariff, electric power service, service to the customer, communication with the customer), in the consumer's satisfaction. The studied company was the Rede Celpa Centrais Elétricas do Pará S.A. In preliminary study an instrumental of measurement of the meaning attributed by the consumer to the term social responsibility was developed (Meaning Social Responsibility Scale), validated with sample of 672 consumers of Belém. This scale was adapted and nominated for Social Responsibility Scale, in order to be used in the present study. They were also built more two instruments (Indicators of Business Acting and Evaluation of Consumer’s Satisfaction) to reach the intended objectives. The rising of the data gave through analysis of existent documents in the company; interviews in depth with the directing category of the company; 595 electric power consumers' residential sampling, residents of the neighborhoods Cremação and Umarizal, in the city of Belém. The data were analyzed through Analysis of Content, Factorial Analysis and Analysis of Multiple and Hierarchical Regression. The fact of dealership Rede Celpa to accomplish stamp actions socially responsible it is not still clearly noticed by her consumer, although they has science that the company accomplishes legal obligations in the employees', consumers’ and environment’s treatment. The variables of business acting attested effect on the consumer's satisfaction, although it has remained a variance margin no explained suggesting the need to explore other antecedent variables. The company had their appraised attributes with concepts varying of reasonable for good for the consumer, what contributes to this to demonstrate moderate degree as for the satisfaction in consuming of this dealership.